ANALISIS WACANA RETORIKA DAKWAH K.H. ABDULLAH GYMNASTIAR - Bahroni Bahroni (INJECT (Interdisciplinary Journal of Communication), 2016)
Indonesia is big country which has biggest Muslim in the world so that dakwah activity is really strategic. Da’wah activities can not be avoided from press. the most well known da’i in public are Abdullah Gymnastiar. This research was objected to describe the grammatical cohesion in their dakwah rhetoric. The procedure to analyze the data were as follow: (1) making into order the data that corresponds the problem answered; (2) Making into units the data based on its order according to the possibilities of category characteristics relation;(3) the interpreting the data score based on the problem that will be answered; (4) the evaluating the range of feasibility and completeness of data related to the problem stretch. The research result covered reference, substitution, elliptics, and conjunction.AbstrakIndonesia merupakan negara besar dengan muslim terbanyak di dunia, maka aktivitas dakwah merupakan hal yang sangat strategis. Aktivitas dakwah tidak luput dari liputan media massa,. Di antara da’i yang sangat dikenal oleh masyarakat adalah Abdullah Gymnastiar. Tujuan penelitian untuk mendeskripsi kan wujud kohesi gramatikal retorika dakwah ketiga tokoh tersebut. Adapun langkah analisis data sebagai berikut: (1) pengurutan data sesuai dengan masalah yang akan dijawab; (2) pembentukan satuansatuan data dalam setiap urutannya sesuai dengan kemungkinan hubungan ciri kategorinya; (3) interpretasi nilai data sesuai dengan masalah yan akan dijawab; (4) evaluasi tingkat kelayakan dan kelengkapan data dikaitkan dengan rentang masalahnya.wacana retorika dakwah tokoh ini mencakup referensi, substitusi, elipsis, dan konjungsi.